2021
DOI: 10.1016/j.jaac.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the Age Limit in Suicide Risk Screening: Clinical Differences and Screening Form Predictive Ability

Abstract: ur research provides preliminary evidence that suicide risk screening is warranted in patients as young as 8-9 years old presenting to the emergency department (ED) with behavioral and mental health symptoms. The goal of this retrospective cohort study (N ¼ 2,466 unique patient visits) was to assess the value of suicide risk screening in children younger than 10 years old who present to the ED with behavioral and mental health concerns. The Johns Hopkins Hospital pediatric ED began screening with the Ask Suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Across ‘psychosocial‐only’ models, higher baseline internalizing symptom severity and younger age at baseline was associated with higher levels of SI and greater severity of internalizing symptoms at follow‐up. Recent research on suicide risk screening has reported that younger patients who present with externalizing symptoms (two characteristics consistent with our findings) and hallucinations, but not with SI or attempts, screened positive for suicide risk, suggesting that screening for suicide risk can be beneficial for children as young as 8 or 9 years of age (Cwik et al., 2021). In the models of psychosocial‐only variables, sex, race/ethnicity (people‐of‐color compared to White participants), the interval between timepoints, and tanner stage (pubertal stage) at follow‐up were associated with increased severity of internalizing severity, but not with increased severity of SI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Across ‘psychosocial‐only’ models, higher baseline internalizing symptom severity and younger age at baseline was associated with higher levels of SI and greater severity of internalizing symptoms at follow‐up. Recent research on suicide risk screening has reported that younger patients who present with externalizing symptoms (two characteristics consistent with our findings) and hallucinations, but not with SI or attempts, screened positive for suicide risk, suggesting that screening for suicide risk can be beneficial for children as young as 8 or 9 years of age (Cwik et al., 2021). In the models of psychosocial‐only variables, sex, race/ethnicity (people‐of‐color compared to White participants), the interval between timepoints, and tanner stage (pubertal stage) at follow‐up were associated with increased severity of internalizing severity, but not with increased severity of SI.…”
Section: Discussionsupporting
confidence: 89%
“…It is well documented that exposure to stressful life events is a potent risk factor for the development of STBs in adolescents (Dykxhoorn, Hatcher, Roy-Gagnon, & Colman, 2017;Miller & Prinstein, 2019), and in particular lifetime sexual/physical abuse, perceived physical safety at school, and parental support are important indicators of SI in pre-adolescents (Walsh, Sheehan, & Liu, 2021). It is possible that participants in our sample (Cwik et al, 2021). In the models of psychosocial-only variables, sex, race/ethnicity (people-of-color compared to White participants), the interval between timepoints, and tanner stage (pubertal stage) at follow-up were associated with increased severity of internalizing severity, but not with increased severity of SI.…”
Section: Contribution Of Psychosocial Variables To the Subsequent Sev...mentioning
confidence: 93%
“…In studies of patients with all chief complaints (including psychiatric and medical/surgical), the positivity rate ranged from 8% ( 6 ) to 29% ( 47 ). In studies that only included patients with psychiatric chief complaints (or studies that included a breakdown of solely psychiatric presentations), positivity rates ranged from 36% ( 20 ) to 66% ( 47 ). In contrast, in studies with patients with only medical/surgical complaints or studies that included a breakdown of solely non-psychiatric presentations, the positivity rates ranged from 3% ( 48 ) to 10% ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in studies with patients with only medical/surgical complaints or studies that included a breakdown of solely non-psychiatric presentations, the positivity rates ranged from 3% ( 48 ) to 10% ( 36 ). A few papers explored the ASQ's effectiveness in screening younger populations, as young as 8 years old ( 6 , 14 , 20 , 22 , 27 ). Those who screen positive on the ASQ tend to be more often female ( 6 , 14 , 20 , 22 , 29 , 42 , 47 ), older ( 14 , 20 , 22 , 29 , 42 ); and, in “all comer” samples, to present with a psychiatric/suicide-related complaint ( 6 , 22 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation